EFEKTIVITAS DAN EFISIENSI KINERJA KEUANGAN PT. BANK SYARIAH MANDIRI TAHUN BUKU 2007, 2008, DAN 2009 - Firmansyah, Farid (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2011)
Financial statement of Banking represents a finance information form able to see performance achievement a bank. While in this research to see effectiveness and efficiency finance performance hence used ratio analysis. Besides, ratio analysis also assists management in comprehending what in fact happened at banking pursuant to a financial statement information, good with ratio comparison now with last and to the next time at internal of banking. Because of activity of banking which concerning society money and trust given, hence each;every banking institute have to make financial statement pursuant to rule from Indonesia Bank as banking supervisor in Indonesia. Besides, good finance performance will be very influecing to at all lenders to entrust its money at the bank. On the contrary, if the bank performance is ugly hence lenders will not hanker to entrust its money at the bank. Financial statement is important is also done as base to make the institute management decision so that target and also expected target can be reached